Innate promiscuity of the CYP706 family of P450 enzymes provides a suitable context for the evolution of dinitroaniline resistance in weed. Issue 6 (6th January 2021) - Abdollahi, Fatemeh; Alebrahim, Mohammad Taghi; Ngov, Chheng; Lallemand, Etienne; Zheng, Yongxiang; Villette, Claire; Zumsteg, Julie; André, François; Navrot, Nicolas; Werck‐Reichhart, Danièle; Miesch, Laurence
Summary: Increased metabolism is one of the main causes for evolution of herbicide resistance in weeds, a major challenge for sustainable food production. The molecular drivers of this evolution are poorly understood. We tested here the hypothesis that a suitable context for the emergence of herbicide resistance could be provided by plant enzymes with high innate promiscuity with regard to their natural substrates. A selection of yeast‐expressed plant cytochrome P450 enzymes with well documented narrow to broad promiscuity when metabolizing natural substrates was tested for herbicide metabolism competence. The positive candidate was assayed for capacity to confer herbicide tolerance in Arabidopsis thaliana . Our data demonstrate that Arabidopsis thaliana CYP706A3, with the most promiscuous activity on monoterpenes and sesquiterpenes for flower defence, can also oxidize plant microtubule assembly inhibitors, dinitroanilines. Ectopic overexpression of CYP706A3 confers dinitroaniline resistance. We show, in addition, that the capacity to metabolize dinitroanilines is shared by other members of the CYP706 family from plants as diverse as eucalyptus and cedar. Supported by three‐dimensional (3D) modelling of CYP706A3, the properties of enzyme active site and substrate access channel are discussed together with the shared physicochemical properties of the natural and exogenous substrates to explain herbicide metabolism.